Quality of life of heroin dependent patients from a drug dependence attention center of Medellin (Colombia) - Tirado Otálvaro, Andrés Felipe; Álvarez Gómez, Matilde Ligia; Velásquez Tirado, Juan david; Lugo, Luz Helena; Giraldo Ferrer, Luis Fernando; Suárez Bermudez, Ana María; Wiedemann, Julieth (Investigación y Educación en Enfermería, 2025)
Objective. To describe the quality of life in terms of health, in the different stages of treatment of patients addict to heroin attended in a drug-dependence attention center of Medellin. Methodology. Cross sectional epidemiological study. 40 heroin addicts in the different stages of treatment: dishabituation, social reinsertion and maintenance program with methadone were interviewed in 2009. The SF-36 instrument for the evaluation of the quality of life and the Zung’s test for depression were used. Descriptive analysis and comparisons through non parametric tests to determine differences among the groups were performed (Group 1: Hospitalized patients, in phase of dishabituation and social reinsertion, and group 2: patients in any of the stages of the methadone’s maintenance program according to the treatment’s phase). Statistical significance was assumed if p<0.05 to determine differences among groups. Results. 40 patients participated (19 in group 1 and 21 in group 2). It was found that the quality of life was better in the patients in group 2 with statistical significant differences for all the domains, except for the physical function and mental health, which from the beginning had higher scores than the 75th percentile. Conclusion. Quality of life is better in patients who have longer time in the maintenance program with methadone.